Energy transfer in ternary TbEDTA chelates with a series of dipicolinic acid derivatives - Räsänen Markus; Takalo Harri; Rosenberg Jaana; Haapakka Keijo; Lukkari Jukka; Kankare Jouko (Elsevier B.V., 2022)
The energy transfer in lanthanoid chelates was studied using the ternary TbEDTA (EDTA ¼ethyl-enediaminetetraacetic acid) chelates with several dipicolinic acid derivatives (pyridine-2,6-dicarboxylic acid (L1, dpa), 4-(9H-fluoren-3-yl)pyridine-2,6-dicarboxylic acid (L2), 4-(dibenzo [b,d]furan-2-yl)pyridine-2,6- dicarboxylic acid (L3), 4-(dibenzo [b,d]thiophen-2-yl)pyridine-2,6-dicarboxylic acid (L4) and 4-(9H-carbazol- 3-yl)pyridine-2,6-dicarboxylic acid (L5)) and spectroscopic methods (absorption and luminescence spectroscopy and the effect of argon treatment and temperature on luminescence lifetime(s)). The results revealed that the ILCT (intra-ligand charge transfer) state is inefficient in exciting the Tb(III) ion and the emissive states of the ligands, as well as the triplet states, act as quenching states by receiving energy back transfer from the Tb(III) ion. The stability constants for these ternary complexes were also determined.